Pyrrole-Based Conjugated Microporous Polymers as Efficient Heterogeneous Catalysts for Knoevenagel Condensation - Gao, Ruidong; Zhang, Guang; Lu, Fanli; Chen, Long; Li, Yang (Frontiers in Chemistry, 2021)
Conjugated microporous polymers (CMPs) with robust architectures, facilely tunable pore sizes and large specific surface areas have emerged as an important class of porous materials due to their demonstrated prospects in various fields, e.g. gas storage/separation and heterogeneous catalysis. Herein, two new pyrrole-based CMPs with large specific surface areas and good stabilities were successfully prepared by one-step oxidative self-polycondensation of 1,2,4,5-tetra(pyrrol-2-ly)benzene or 1,3,5-tri(pyrrol-2-ly)benzene, respectively. Interestingly, both CMPs showed very high catalytic activity toward Knoevenagel condensation reaction, which was attributed to the inherent pore channels, high specific surface areas and abundant nitrogen sites within CMPs. Additionally, both CMPs displayed excellent recyclability with negligible degradation after 10 cycles. This work provides new possibilities into designing novel nitrogen-rich high-performance heterogeneous catalysts.